O livro didático e o discurso do professor no ensino das operações com números inteiros para alunos do E.J.A - Silva, Alessandro Rosa (2006)
The purpose of this work was to investigate the role of language in the process of teaching integer numbers operations within the Young and Adult Education, specifically the aspect of comprehension of the established dialog by teachers or by text books. Our framework is based on Grice, according to this author there is a set of principles that guides the speaker s action through an efficient use of language for cooperative aims. Those Conversation Principles specify how participants should act in a conversation. Our questions include 1) What is the environment proposed by teachers in classroom? 2) Which material are used in classroom? How is cooperation been established by the teacher and the used material according to Grice? Two questionnaires were elaborated and applied with twelve teachers. Results from analysis of questionnaire revealed that teachers were not cooperating in classrooms. Six different collections of text books were also analyzed and again failed in pursuing a clear dialog with lector. Those findings lead us to further discuss a different environment where dialog is the main concern and to present an alternative for introducing integer numbers and operations